IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG PASAR SELODANG KELAPA OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN INDRAGIRI HILIR - Candra Saputra; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Selodang Kelapa Market is the largest market in Indragiri Hilir regency who shaped existence of floating market in Tembilahan, while there are some problems happend for Department of industry and trade Indragiri Hilir Regency. The merchant market that still put the merchandise in the land park and the funds budgeted for the facilities of the market made traders It is still minimal. This research aims to look at how Structuring the market Selodang Kelapa Tembilahan as a market that has a floating building can be well-ordered. This research uses qualitative research methods by examining the descriptive data according to the concepts of the theory of implementation. In data collection, researchers use interview techniques, observation and documentation. These researchers also use key informants as a source of information and as a source of triangulation technique in testing kevaliditan data. The results of this study indicate that the structuring the market does not run properly. This is proven by the communication, resources, Disposition and organizational structure is still not optimal. Restricting factors in structuring the market traders, namely budget, Policy Evaluation and the construction of the merchant Market Selodang Kelapa. This is caused due to lack of support and lack of assistance from the Government of the State of Indragiri District thus making a market trader of selodang Kelapa Structuring has not been optimal.Keywords: Structuring, Traders, Selodang Kelapa Market